Comparative evaluation of DFDBA versus PRF with DFDBA in treatment of grade-II furcation defects - A clinical trial - Kinjal N Desai; Rohit R Thakkar; Jalpa Patel; Ekta Gupta; Namrata Trivedi; Dipali Sampat (Wolters Kluwer Medknow Publications, 2024)
Background: In order to determine whether a method is more successful for treating a grade-II furcation deficiency, this randomized trial will compare demineralized freeze-dried bone allograft (DFDBA) to platelet-rich fibrin with DFDBA. Materials and Methods: Twenty systematically healthy patients between the ages of 30 and 60 with a grade-II furcation were evaluated pre and postoperatively for changes in the modified plaque index, probing depth, relative vertical and horizontal clinical attachment level, gingival marginal level, and radiographic bone defect. Results: The test group significantly outperformed the control group on all clinical and radiological measures. Conclusion: The experimental group improved at both clinical attachment levels and had a higher decrease in probing depth than the control group did.